Vanadium pentoxide nanochains for high-performance electrochemical supercapacitors - Umeshbabu, Ediga; Ranga Rao, G. (Journal of colloid and interface science, 2016)
[Display omitted] •Synthesis of V2O5 nanochains for charge storage applications.•Hydrothermal medium with CTAB surfactant is crucial to obtain V2O5 nanochains.•Capacitance of bulk V2O5<agglomerated V2O5 particles<V2O5 nanochains. We have synthesized unique hierarchical one dimensional (1D) nanochains of V2O5 by employing simple hydrothermal method using cetyltrimethylammonium bromide (CTAB) as a soft template. The electrochemical performance of resulting V2O5 electrode materials was evaluated by cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance spectroscopy techniques. The V2O5 nanochains (V2O5-ctab) show maximum specific capacitance of 631Fg−1 at a current density of 0.5Ag−1 and retain 300Fg−1 even at high current density of 15Ag−1. In addition the V2O5 nanochains show good cyclic stability with 75% capacitance retention after 1200 charge-discharge cycles. The order of specific capacitance is commercial bulk-V2O5 (160Fg−1)<agglomerated V2O5 particles (395Fg−1)<V2O5 nanochains (631Fg−1). The interconnected nanochain-like morphology and high specific surface area are the main factors which contribute to higher electrochemical performance to V2O5 nanochains and promote facile exchange of Li+ ions during the charge-discharge processes.